2013
DOI: 10.3174/ajnr.a3531
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Evaluation of Arterial Wall Response to 5 Neurovascular Mechanical Thrombectomy Devices in a Swine Model

Abstract: BACKGROUND AND PURPOSE:Five commercial devices are available for mechanical thrombectomy in acute ischemic stroke. This study evaluated and compared the resultant arterial damage from these devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 26 publications
4
82
0
Order By: Relevance
“…These included 5 patients treated for MCA M1 occlusion; 3, for ICAT occlusion; and 2, for ICA tandem occlusion, which overall represented 4.3% of all patients undergoing anterior circulation MT procedures during the analyzed time (see above). The median baseline NIHSS score was 16 (interquartile range, [13][14][15][16][17][18][19], and the median time from symptom onset to the start of the MT procedure was 168 minutes (interquartile range, 150 -179 minutes). For both ICA tandem occlusions, proximal ICA stent placement was performed before MT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These included 5 patients treated for MCA M1 occlusion; 3, for ICAT occlusion; and 2, for ICA tandem occlusion, which overall represented 4.3% of all patients undergoing anterior circulation MT procedures during the analyzed time (see above). The median baseline NIHSS score was 16 (interquartile range, [13][14][15][16][17][18][19], and the median time from symptom onset to the start of the MT procedure was 168 minutes (interquartile range, 150 -179 minutes). For both ICA tandem occlusions, proximal ICA stent placement was performed before MT.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical or intracranial vessel trauma remains a potentially serious procedure-related adverse event, which occurs at a low incidence with the use of the standard single SR MT technique. 3,5,10,15,16 In the Solitaire FR With the Intention For Thrombectomy trial, the reported incidences of arterial dissection, symptomatic cerebral hemorrhage, and SAH were 4.5%, 1.1%, and 1.1%, respectively. 15 The use of 2 parallel SRs within the MCA or ICA vessel lumen may potentially increase the force on the endothelium during the retrieval maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…These delayed arterial abnormalities are of unknown pathophysiologic etiology but may illustrate device-related arterial wall damage, which, up to now, was mainly reported in histopathologic animal studies. 18,6 Pre-existing stenosis did not appear to have worsened at 1-year FU or to be likely after MET. All arterial abnormalities remained asymptomatic during the FU period, and no independent predictor of arterial abnormality was identified.…”
Section: Discussionmentioning
confidence: 99%
“…6 The only published short-term angiographic follow-up study after MET by using various devices reported 0.9% arterial occlusion and 3.4% de novo stenosis. All cases were asymptomatic and identified as a consequence of arterial wall damage likely due to MET.…”
mentioning
confidence: 99%
See 1 more Smart Citation